Hepatitis B and C in household and health services solid waste workers - Marcos Paulo Gomes Mol; Dirceu Bartolomeu Greco; Sandy Cairncross; Leo Heller (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract Human contact with solid waste poses biological, chemical, and physical health risks for workers involved in waste collection, transportation, and storage. The potential risk to human health resulting from contact with health services waste or household waste still sparks considerable controversy. The aim of this study was to identify the context of scientific discussions on risk/infection from the hepatitis B and C viruses in workers that collect solid waste from health services or households. The search covered publications up to 2013 in Brazilian and international databases, and 11 articles were selected through a literature review. Of these, six conclude that there is an increased risk of infection in workers that collect household waste when compared to those unexposed to waste, three point to greater risk for workers that collect health services waste as compared to those that collect ordinary waste, and the other two found no difference between exposed and unexposed individuals.